FTIR spectroscopy and Optimization of Biosurfactant Production by Lactobacillus acidophilus andLactobacilluspentosus (Albayan Scientific Journal, 2023)
Two Lactobacillus strains (L. acidophilus and L. pentosus) isolated from dairy products, showed good biosurfactant properties. The purpose of this work was to optimize of biosurfactant production by L.  acidophilus and L. pentosus and to characterize thesebiosurfactant by FTIR spectroscopy. Maximumbiosurfactant production was achieved when the two isolates grown at pH 7 and 6, incubated at 37 ºC and 36 ºCfor 24 h, 150 rpm and 2% of NaCl respectively. Types of cooking oil as a carbon source and nitrogen source significantly (p
Keywords: Biosurfactant; acidophilus; pentosus; EmulsificationIndex; tension; lipopeptides; glycolipids